Spider in the well - Hannigan, Jess (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2024)
"Breaking News: Wishing Well Broken! The townspeople of Bad Göodsburg are up in arms. With their beloved well busted, none of their important, generous, kindhearted wishes are coming true! Time to send that good-for-nothing Newsboy to investigate..."--